Identitas Kota: Pembangunan Imaji Kota melalui Karya Seni di Ruang Publik - Budi Adi Nugroho (JURNAL RUPA, 2018)
City has a character that reflects the inhabitants and idealism of leaders who try to shape the image of their city. Imagery or images would later describe a city as a whole in a certain picture that put the city in the scale fromthe smallest to global regions. The control upon its image is carried out with image management that appears in the front corridors of the city, as is done by the City of Bandung in building the image of the city as a positioning strategy for the part of the world's creative and design cities. The research method will use interdisciplinary research, involving anthropological approaches, material exploration, and fine art works. Public understanding, decision makers up to the capital are needed in supporting the development of the image of the city. The level of importance in understanding the work of art in the public space as one component that can help build the image of the city of Bandung. This research will produce work proposals that can help support the overall image of the city of Bandung that is integrated with the character and development of the city. Keywords: city, identity, management, Bandung, space, public art